Pengaruh Terapi Family Psychoeducation (FPE) Terhadap Kemampuan Keluarga Merawat Anggota Keluarga Dengan Gangguan Jiwa - Sulistyowati, Ni Made Dian (Coping: Community of Publishing in Nursing, 2015)
The  role  of  the  family  in  the  treatment  of  family  members  with  mental  disorder  becomes important  where  individuals  initiate  interpersonal  relationships  within  the  family environment.  The  role  of  the  family  since  the  beginning  of  the  client  at  the  hospital  will increase  the  success  of  treatment  and  the  ability  of  families  to  care  for  clients.  Hence  the need  for  knowledge  of  the  family  to  the  healing  process  of  handling  family  members  with mental disorder  while  in the hospital and within the community  so that  families are  better prepared for the client’s condition and help them become more independent and productive. This study aims to look at the effectiveness of family psychoeducation (FPE) therapy on the ability of families in caring the family members with mental disorder. The study design used a quasi-experiment  design  (50  in  the  experimental  group,  50  in  the  control  group).  The  test results  obtained  statistically  significant  relationship  between  FPE  therapy  on  cognitive abilities  and  psychomotor  families  in  caring  family  members  with  mental  disorders  (p <0.05). The results of the study have shown that FPE therapy is effective in increasing the family ability such as psychomotor and cognitive in caring the family members with mental disorder.
Keywords: family psychoeducation therapy; cognitive ability; psychomotor ability